Pathogenic Stress Induces Human Monocyte to Express an Extracellular Web of Tunneling Nanotubes - Shahar, Michal; Szalat, Auryan; Rosen, Haim (Frontiers in Immunology, 2021)
Actin-based tunneling nanotubes are a means of intercellular communication between remote cells. In the last decade, this type of nanotube was described in a wide variety of cell types and it became widely accepted that communication through these nanotubes is related to response to environmental changes. Few reports, however, are available regarding the expression of similar nanotubes in vivo or in primary cells. Moreover, the functional significance of this intercellular communication for health and disease is largely unknown. In this context, and as a first step in unraveling these questions, we examined the formation of similar nanotubes in primary peripheral human monocytes. To that end, we combined the use of a live cell imaging system along with advanced methods of fluorescent and scanning electron microscopy. This experimental approach reveals for the first time that the bacterial lipopolysaccharide endotoxin induces a transient expression of an unexpected abundance of actin-based tunneling nanotubes associated with vesicles. In addition, it was found that a similar response can be achieved by treating human monocytes with various bacterial and yeast membrane components, as well as with a viral component analog. In all these cases, this response is mediated by distinct complexes of toll-like receptors. Therefore, we suggest that the observed phenomena are related to a broad type of monocyte pathogen response, and raise the possibility that the phenomena described above may be involved in many clinical situations related to inflammation as a new topic of study.